Seroprevalence of pathogenic Leptospira serogroups in asymptomatic domestic dogs and cats: systematic review and meta-analysis - Ricardo, Tamara; Azócar-Aedo, Lucía Isabel; Previtali, María Andrea; Monti, Gustavo (Frontiers in Veterinary Science, 2024)
Leptospirosis is a neglected zoonotic disease transmitted by contact with urine of animals infected with pathogenic species of the bacteria Leptospira or by contact with environments contaminated with the bacteria. Domestic dogs and cats may act as reservoirs or as sentinels of environmental contamination with leptospires, posing a public health concern. There is a great diversity of leptospires, and one common way to classify them is into serogroups that provide some information on the host species they are associated with. The aims of this study were: 1) to quantitatively summarize the overall prevalence and serogroup-specific prevalence of antibodies against pathogenic leptospires in asymptomatic dogs and cats, and 2) to identify environmental and host characteristics that may affect the prevalence. Three electronic databases and the reference lists of eligible articles were screened, for epidemiological studies conducted between the years 2012-2022. We estimated overall and serogroup-specific prevalence using three-level meta-analysis models and assessed potential sources of heterogeneity by moderator analysis and meta-regression. Eighty-four studies met the inclusion criteria (dog studies 66.7%, cat studies 26.2%, both species 7.1%). There were significant differences between dogs and cats in the overall prevalence model (P<0.001), but not in the serogroup-specific model (P>0.05). In dogs, the prevalence of Leptospira interrogans serogroup Canicola was significantly higher when compared to other pathogenic serogroups (P<0.001), while in cats there were no significant differences among serogroups (P = 0.373). Moderator analysis showed that the prevalence of L. kirschneri serogroup Grippotyphosa was significantly higher in stray/sheltered dogs than in domiciled dogs (P = 0.028). These results suggest that pathogenic serogroups associated with small mammals are circulating among asymptomatic pets and should be taken into account in the transmission cycle of leptospires, as well as in the standard MAT panel for diagnosis in dogs and cats. It also highlights the importance of including both dogs and cats as potential reservoirs when conducting eco-epidemiological studies in different geographical and ecological areas.